CO Observations of the Type Ia Supernova Remnant 3C 397 by the Nobeyama 45 m Radio Telescope: Possible Evidence for the Single-degenerated Explosion - Ito, D.; Sano, H.; Nakazawa, K.; Mitsuishi, I.; Fukui, Y.; Sudou, H.; Takaba, H. (The Astrophysical journal, 2025)
We present a new CO observation toward the Type Ia supernova remnant 3C 397 using the Nobeyama 45 m radio telescope at an unprecedented angular resolution of  ∼18″. We newly found that the CO cloud at V LSR = 55.7–62.2 km s −1 (60 km s −1 cloud) shows a good spatial correspondence with the radio continuum shell. We also found an expanding gas motion of the 60 km s −1 cloud with an expansion velocity of  ∼3 km s −1 , which is thought to be formed by the pre- and/or postsupernova feedback. By considering the positions of Galactic spiral arms and the X-ray/H i absorption studies, we concluded that 3C 397 is physically associated with the 60 km s −1 cloud rather than the previously known CO cloud at V LSR  ∼ 30 km s −1 . Given that the previously measured preshock density is  ∼2–5 cm −3 , the expanding motion of the 60 km s −1 cloud was likely formed by the presupernova feedback known as optically thick wind. The scenario is consistent with the fact that 3C 397 exploded inside a wind-blown bubble as a single degenerate system.